Top 7,000 & next 5,000 corporations business profiles 2000-2001. (Philippine Business Profiles and Perspectives, Inc., 2000)
This CD-ROM contains a database of top 12,000 corporations from 1998 to 1999, list of industry standards and company profiles. Articles and past databases of top 12,000 corporations are also included.